Energy Balance–Related Behaviors, Perinatal, Sociodemographic, and Parental Risk Factors Associated with Obesity in Italian Preschoolers. (18th May 2016) - Shashaj, Blegina; Graziani, Maria P.; Contoli, Benedetta; Ciuffo, Cristina; Cives, Claudia; Facciolini, Sandra; Rigoni, Maria L.; Spaterna, Stefania; Taucci, Mauro; Raponi, Massimiliano; Manco, Melania
Abstract : Objective: The obesity epidemic stems from the complex interplay between genetics and environmental factors. Identifying age-specific risk factors in preschoolers may allow implementing more effective intervention strategies. The aim of the present investigation was to examine the association of overweight/obesity with several perinatal, parental, socioeconomic status (SES), and lifestyle-related risk factors in a large sample of Italian preschoolers. Methods: One thousand eleven children (age 2.0 to 5.7 years) were included in the study. Family pediatricians measured weight and height and collected information on obesity risk factors by means of questionnaires. Perinatal risk factors were recalled from electronic medical records. Weight status was defined according to cutoffs of the International Obesity Task Force (IOTF). Results: Seven hundred sixty-four children (75.6%) were normal weight, and 247 (24.4%) were overweight/obese. Multivariate analysis showed that skipping breakfast (odds ratio [OR] = 3.7; 95% confidence interval [CI], 1.32–10.51), daily drinking of sugar-sweetened beverages (OR = 2.0; 95% CI, 1.02–4.03), meat consumption <5 times/week (OR = 2.2; 95% CI, 1.11–4.57), and formula feeding (OR = 2.1; 95% CI, 0.8–4.5) were significantly ( p < 0.05) associated with increased risk of obesity. Conclusions: Though exclusive formula or mixed feeding represents an age-specific risk factor for overweight/obesity, lifestyle factors associated with increased risk in Italian preschoolers include habits that are common to school-age children, such as skipping breakfast and consumption of sugar-sweetened beverages. The reduced consumption of meat emerged as a risk factor for overweight/obesity, but future research is required to better understand this relationship. Our data suggest, on the whole, that prevention of such unhealthy behaviors must be pursued in preschoolers by means of age-specific interventions.